Core Convergence Without Monotone Preferences or Free Disposal - Alejandro Manelli (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
We prove some core convergence theorems for finite economies without monotone preferences or free disposal of commodities. When these assumptions are relaxed, the relationship between the continuum and the large finite economies is lost. Extra conditions are needed, in general, to obtain convergence results.
Keywords: 330